ACSL4 predicts rapid kidney function decline in patients with diabetic kidney disease - Rui Shen; Xin Yu; Caifeng Shi; Yi Fang; Chunsun Dai; Yang Zhou (Frontiers in Endocrinology)
BackgroundFerroptosis of kidney tubular epithelial cells contributes to the pathogenesis of diabetic kidney disease (DKD). An increase in the enzyme long-chain fatty acid CoA ligase 4 (ACSL4) favors ferroptosis. However, the association between ACSL4 in renal tubules and kidney outcomes of patients with DKD is unknown.MethodsTo investigate the predictive property of ACSL4 in rapid kidney function decline in patients with DKD, a retrospective cohort of 72 biopsy-proven DKD patients were enrolled and followed up for a median of 23 months. Tubular expression levels of ACSL4 in the renal biopsy specimens from 72 DKD patients and 12 control subjects were measured using immunohistochemistry staining. The associations between the ACSL4 level and clinical characteristics as well as rapid kidney function decline defined as an estimated glomerular filtration rate (eGFR) slope ≤ -5 ml/min/1.73m2/year were analyzed.ResultsACSL4 was mainly expressed in tubular epithelial cells. The tubular ACSL4 expression levels in the DKD patients were significantly higher than those in the control subjects. ACSL4 was positively correlated with proteinuria and negatively correlated with albumin and hemoglobin at the time of the renal biopsy. During the follow-up time period, the median eGFR slope of these DKD patients was -2.30 ml/min/1.73m2/year. ACSL4 was negatively correlated with the eGFR slope. The top tertile of baseline ACSL4 was found to identify the subjects with DKD who were at high risk for rapid kidney function decline and a similar significant relationship was found using ACSL4 levels as a continuous variable.ConclusionsACSL4 was associated with a rapid progression of DKD and may serve as a novel pathological biomarker.